2022
DOI: 10.12775/jehs.2022.12.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Electronic forms of entertainment in the context of physical activity and addiction risk – a knowledge review

Abstract: A new way of spending leisure time browsing the Internet, using social networking sites, and playing games has created a new health problem: cell phone addiction. So-called phonoholism or netholism is most thriving among young people, who prioritize entertainment in the real world, which most often necessitates physical activity, over entertainment in the virtual world, which requires a more static approach. However, some companies have gone against the traditional use of phone games by creating multimedia cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Nabídka nelegálních drog se na trhu neustále mění a neinformovaný vychovatel může snadno přehlédnout známky blížícího se adiktologického problému. Nelze opomenout současný gradující problém nelátkových závislostí, zejména na sociálních sítích a na virtuálním prostředí (Grajek, 2022). Alarmující zjištění jsme zaznamenali v oblasti reflexe respondentů na jejich roli v edukačním procesu.…”
Section: Průběh Výzkumu Významná Zjištěníunclassified
“…Nabídka nelegálních drog se na trhu neustále mění a neinformovaný vychovatel může snadno přehlédnout známky blížícího se adiktologického problému. Nelze opomenout současný gradující problém nelátkových závislostí, zejména na sociálních sítích a na virtuálním prostředí (Grajek, 2022). Alarmující zjištění jsme zaznamenali v oblasti reflexe respondentů na jejich roli v edukačním procesu.…”
Section: Průběh Výzkumu Významná Zjištěníunclassified
“…If we truly want to understand the motivational structure of exercisers, we should examine the entire age span and include youth as well. One of the reasons for this is that many studies have shown that the motivation for exercise varies according to age group (Biddle et al, 2003;Trujillo et al, 2004;Caglar et al, 2009;Brunet and Sabiston, 2011;Egli et al, 2011;Molanorouzi et al, 2015;Jones et al, 2020;Box et al, 2021;Grajek et al, 2021;Gut et al, 2022;Rodrigues et al, 2022), so that the assessment of motivational structures between different exercise modalities would lead to biased results in older adults. Another advantage of including young adults in the study is the fact that they can be guided toward a more active lifestyle, if this is not already the case.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancement facilitates human progress in broader aspects. It has changed the way of our lifestyle in different domains such as health (Ahorsu et al, 2020;Rajabi et al, 2020;Renu, 2021), entertainment (Grajek, 2022;Renu, 2021), and commerce (Beer and Mulder, 2020;Jongwanich et al, 2022;Renu, 2021). Despite the several advantages, the technology adversely affects the user's psychological health (Chen et al, 2020;Chen et al, 2021;Fazeli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%